Optimizing the Role of Administration in Improving Student Administrative Services at the Titian Ilmu Pengabuan Foundation High School, West Tanjung Jabung Regency - Putri Putri; Tuti Indriyani; Sri Ramdayeni Sakunti (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study is motivated by the suboptimal implementation of student administrative services at SMA Yayasan Titian Ilmu Pengabuan, Tanjung Jabung Barat Regency. The problems are caused by the limited number of administrative staff, the absence of a head of administration, and inadequate supporting facilities. These conditions lead to delays in administrative services and less effective management of student data. This study aims to examine the role of administrative staff, the obstacles encountered, and the efforts made to improve student administrative services. This research employs a descriptive approach using a qualitative method. The research subjects consist of the principal, two administrative staff members, and three students. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that administrative staff play an important role in student administrative services, including managing student data, archiving documents, issuing certificates, legalizing documents, and providing academic information. The services are considered fairly good; however, there are still obstacles such as limited human resources and inadequate facilities. Efforts to improve services include task distribution, strengthening teamwork, and increasing responsiveness to students’ needs.